STRATEGI PENGEMBANGAN BUSINESS MODEL CANVAS PADA PROGRAM SAPI KERBAU KOMODITAS ANDALAN NEGERI (SIKOMANDAN) - Iman Trisman; Puradireja Rino Hadiwijaya; Firman Achmad; Herlina Linda (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The purpose of this study is to evaluate the government program for the Sapi Kerbau Komoditas Andalan Negeri (SIKOMANDAN) Government flagship program 2020. This research was conducted by survey method, data collection was collected through literature study from various sources related to the research. The data analysis method uses Business Model Canvas analysis (BMC) and SWOT analysis. The results of the study indicate that there are nine strategies that must be carried out, namely; (1) using estrus synchronization technology on extensive rearing land; (2) Value proposition by involving local governments both in terms of budgeting and supporting activities; (3) Channels by issuing regulations that can facilitate the central government to obtain data and information related to the SIKOMANDAN program; (4) Relations by utilizing social media to communicate from the central government to local governments, as well as breeders; (5) Value Stream-Returns by creating a system that can synergize the reporting of four business processes; (6) Key resources by utilizing resources in each province/district/city. (7) Key Activities by integrating all existing business processes; (8) Key Partnership by participating in the preparation of government regulations; (9) Value Stream-Outlay and Costs by making programs. It is hoped that in the future this strategy will be able to be implemented and recorded in the guidelines for the Outline of the Work Program if there are structural changes.